Troponins and brain natriuretic peptides for the prediction of cardiotoxicity in cancer patients: a meta‐analysis. (12th November 2019) - Michel, Lars; Mincu, Raluca I.; Mahabadi, Amir A.; Settelmeier, Stephan; Al‐Rashid, Fadi; Rassaf, Tienush; Totzeck, Matthias
Abstract: Aims: Cardiac biomarkers are a mainstay in diagnosis of cardiovascular disease but their role in cardio‐oncology has not yet been systematically evaluated. This meta‐analysis aims to determine whether cardiac troponins and (N‐terminal pro) brain natriuretic peptide (BNP/NT‐proBNP) predict cancer therapy‐related left ventricular (LV) dysfunction. Methods and results: Scientific databases were searched for studies that assessed troponins or BNP/NT‐proBNP in adult patients undergoing cancer therapy. Data from 61 trials with 5691 patients were included. Cancer therapy was associated with an increase in troponin levels [odds ratio (OR) 14.3, 95% confidence interval (CI) 6.0–34.1; n = 3049]. Patients with elevated troponins receiving chemotherapy or human epidermal growth factor receptor 2 inhibitor therapy were at higher risk for LV dysfunction (OR 11.9, 95% CI 4.4–32.1; n = 2163). Troponin had a negative predictive value of 93%. Mean BNP/NT‐proBNP levels were increased in patients post‐treatment (standardized mean difference 0.6, 95% CI 0.3–0.9; n = 912), but the available evidence did not consistently indicate prediction of LV dysfunction (OR 1.7, 95% CI 0.7–4.2; n = 197). β‐blocker and angiotensin‐converting enzyme inhibitor therapy to mitigate cardiotoxicity during cancer therapy was associated with a decline in serum troponins (OR 4.1, 95% CI 1.7–9.8; n = 466). Conclusion: Elevated troponin levels predict LV dysfunction in patients receiving cancer therapy. Assessment of troponin levels may qualify as a screening test to identify patients who require referral to cardio‐oncology units and benefit from preventive strategies. Further evidence is required for both biomarkers.